2005
DOI: 10.1107/s1600536805041760
|View full text |Cite
|
Sign up to set email alerts
|

Bis[3-acetyl-6-methyl-2H-pyran-2,4(3H)-dionato]bis(dimethyl sulfoxide)copper(II)

Abstract: Key indicatorsSingle-crystal X-ray study T = 294 K Mean (C-C) = 0.003 Å R factor = 0.035 wR factor = 0.093 Data-to-parameter ratio = 22.6 For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
(8 reference statements)
2
6
0
Order By: Relevance
“…The Cu1ÐO4A and Cu1ÐO4B bond distances (from DMSO) (Table 1) in (I) fall within the range 2.34±2.46 A Ê (Cu1ÐO4A is slightly shorter) found for octahedral copper(II) complexes containing DMSO in axial positions (Benali-Cherif et al, 1995;Bieller et al, 2005;Djedouani et al, 2006;Chan et al, 1996). The longest CuÐO(DMSO) bond in the previously reported complexes is 2.463 A Ê in bis[3-acetyl-6-methyl-2H-pyran-2,4(3H)-dionato]bis(dimethyl sulfoxide)-copper(II) (Djedouani et al, 2006), re¯ecting Jahn±Teller distortion.…”
Section: Commentmentioning
confidence: 61%
See 1 more Smart Citation
“…The Cu1ÐO4A and Cu1ÐO4B bond distances (from DMSO) (Table 1) in (I) fall within the range 2.34±2.46 A Ê (Cu1ÐO4A is slightly shorter) found for octahedral copper(II) complexes containing DMSO in axial positions (Benali-Cherif et al, 1995;Bieller et al, 2005;Djedouani et al, 2006;Chan et al, 1996). The longest CuÐO(DMSO) bond in the previously reported complexes is 2.463 A Ê in bis[3-acetyl-6-methyl-2H-pyran-2,4(3H)-dionato]bis(dimethyl sulfoxide)-copper(II) (Djedouani et al, 2006), re¯ecting Jahn±Teller distortion.…”
Section: Commentmentioning
confidence: 61%
“…The Cu1ÐO4A and Cu1ÐO4B bond distances (from DMSO) (Table 1) in (I) fall within the range 2.34±2.46 A Ê (Cu1ÐO4A is slightly shorter) found for octahedral copper(II) complexes containing DMSO in axial positions (Benali-Cherif et al, 1995;Bieller et al, 2005;Djedouani et al, 2006;Chan et al, 1996). The longest CuÐO(DMSO) bond in the previously reported complexes is 2.463 A Ê in bis[3-acetyl-6-methyl-2H-pyran-2,4(3H)-dionato]bis(dimethyl sulfoxide)-copper(II) (Djedouani et al, 2006), re¯ecting Jahn±Teller distortion. The Cu1ÐO4A bond (from the major DMSO component) in (I) differs slightly from the corresponding bond in hexakis(dimethyl sulfoxide)copper(II) bis(hydrogensulfate) [2.34 (1) A Ê ; Bieller et al, 2005] and from that observed in bis[2,4-diamino-6-(4-pyridyl)-1,3,5-triazine]bis(dimethyl sulfoxide)copper(II) perchlorate [2.353 (9) A Ê ; Chan et al, 1996].…”
Section: Commentmentioning
confidence: 61%
“…It is important to make clear that the H5-H10 distance is very similar between all the possible bipyramidal Zn complexes. Despite the inexistence of the octahedral complexes Zn(DHA) 2 (py) 2 and Zn(DHA) 2 (-pic) 2 , we studied them by molecular modeling in order to compare their potential structural data with the respective bipyramidal complexes [2,[34][35][36]. The modeling of octahedral Zn complexes indicated that their H5-H10 distances correspond to 3.765 Å, which is approximately 35% shorter than the calculated value for the bipyramidal complexes (5.83 Å).…”
Section: Resultsmentioning
confidence: 99%
“…For related literature, see: Arndt et al (1936); Casabó et al (1987); Djedouani et al (2006); Gelasco et al (1997); Zucolotto Chalaça et al (2002).…”
Section: Related Literaturementioning
confidence: 99%
“…As an extension of our work (Djedouani et al, 2006), we present here the synthesis and crystal structure determination of [Cu(DHA) 2 (DMF) 2 ] (I), which molecular structure is illustrated in Fig. 1.…”
Section: S1 Commentmentioning
confidence: 99%